Instructional leadership practices of primary school leaders in Petaling Perdana District, Selangor / Edward Devadason Yanakan Yowan - Edward Devadason, Yanakan Yowan (2019)
According to the Malaysian Education Blueprint 2013-2025, instructional leadership is seen as fundamental for school achievements. This is given high consideration in the preparation of school leaders through NPQEL, as well as through professional development programs for those senior school leaders who have not been through the NPQEL program. In view of the inadequate contribution to the knowledge base on instructional leadership in Malaysia, and the limited evidence base, this research examined the understanding and practices of Instructional Leadership among the primary school leaders in Petaling Perdana District, Selangor. Their view and roles as instructional leaders, description of instructional leadership practice in school context and the important aspects of instructional leadership as perceived among teachers is explored in this research. This study adopted a qualitative research design, semi-structured interviews with 24 primary school principals and 4 focus group teachers. Results showed that Hallinger and Murphy’s Instructional leadership Model (1985) is moderately reflected in the principals’ practice. On the other hand, evidence from the inductive analysis indicates that the dimension reflected in Murphy’s Comprehensive Instructional Leadership Framework (1990) which derived from a comprehensive review of literature on instructional leadership of principals in effective schools where the quality of teaching and learning was highly reflected. Evidence from the inductive analysis also further indicate that Malaysian principals practice few functions of instructional managers such as fulfilling Ministry expectations, role modelling, having a sense of responsibility and employs managerial assertiveness towards an effective schools and improving teaching and learning. Findings from the focus group on the instructional leadership practices of the principals as perceived by the teachers during the focus co-relate with the principal’s responses. The findings of this study provides contemporary knowledge base about instructional leadership in Malaysia.